2020
DOI: 10.1111/jce.14488
|View full text |Cite
|
Sign up to set email alerts
|

Increases in repolarization heterogeneity predict left ventricular systolic dysfunction and response to cardiac resynchronization therapy in patients with left bundle branch block

Abstract: Introduction This study aimed to investigate the association between T‐wave morphology and impaired left ventricular ejection fraction (LVEF) in patients with complete left bundle branch block (cLBBB), and the predictive value of T‐wave morphology for response to cardiac resynchronization therapy (CRT). Methods and Results We enrolled 189 patients with cLBBB on electrocardiogram performed between January 2007 and December 2011 who underwent standard echocardiography. Repolarization parameters, including the QR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Sauer et al reported an independent relationship between TpTe and radial SD-tPkS (measuring contraction duration heterogeneity on echocardiography) ( Sauer et al, 2014 ). In addition, DVR was found to be significantly correlated with impaired LVEF ( Huang H. C. et al, 2020 ). However, whether repolarization parameters were associated with LBBAP response remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Sauer et al reported an independent relationship between TpTe and radial SD-tPkS (measuring contraction duration heterogeneity on echocardiography) ( Sauer et al, 2014 ). In addition, DVR was found to be significantly correlated with impaired LVEF ( Huang H. C. et al, 2020 ). However, whether repolarization parameters were associated with LBBAP response remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the T-wave and Tp-e interval, easily measurable ECG parameters, were taken into consideration. Despite the fact that there is no certain evidence that the increased T-wave duration implies an unfavorable CRT response, it was reported in the literature that the T-wave area and its morphology have been associated with prognosis in patients with HFrEF who underwent CRT [18,19]. In addition, new measurement methods that utilize automatic ECG programs such as absolute T-wave residuum, T-wave morphology dispersion and T-wave loop area, have been found to be effective in predicting the CRT response [19].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that there is no certain evidence that the increased T-wave duration implies an unfavorable CRT response, it was reported in the literature that the T-wave area and its morphology have been associated with prognosis in patients with HFrEF who underwent CRT [18,19]. In addition, new measurement methods that utilize automatic ECG programs such as absolute T-wave residuum, T-wave morphology dispersion and T-wave loop area, have been found to be effective in predicting the CRT response [19]. Nonetheless, these complex measurement methods need special computer programs and are difficult to be performed during the daily clinical practice when evaluating the CRT response at the bedside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Ventricular repolarization heterogeneity has an important role in the development of HF, and several repolarization heterogeneity markers like the T-wave area, increased QRS-T angle, and T-wave morphology dispersion have been reported to have a prognostic impact on clinical outcomes. 19,20 Maffessanti et al found that discordant T waves in LBBB patients are explained by interventricular dispersion in repolarization by electro-anatomic mapping. 21 In our study, the presence of dLBBB was associated with a higher risk of cardiovascular death or non-fatal HF hospitalization.…”
Section: Plausible Mechanisms Of Discordant Left Bundle Branch Block ...mentioning
confidence: 99%